Management of bacterial leaf blight disease of rice in farmer’s field condition at Bhaktapur district of Nepal - Sharma, Patiksha; Baidya, Suraj; Kandel, Saraswoti; Chaudhary, Suraj; Magar, Prem Bahadur (Journal of Agriculture and Natural Resources, 2022)
Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae is considered as one of the major threats to rice production in Nepal. To identify the effective control measures, an experiment was done in a randomized complete block design with three replications in a farmer's rice field at Bhaktapur, during the summer seasons of 2018 and 2019. Three plants extracts; 1% Neem extract, 2% Asuro leaf extract, and 2% Titepati leaf extract along with two fungicides viz. 0.1% Agricin and 0.2% Blitox 50, and one bio-control agent 1%Kisan Pseudomonas were used as treatments. The first spray was given as a prophylactic spray at the jointing stage, and they were applied 3 times at 50, 60 and 70 days interval. All the treatments significantly reduced disease and improved test weight higher than control. Among the tested treatments, 0.1% Agricin performed as the best with 65.70% disease control and increase in yield over control by 28.13%. Among the tested botanicals, 2% stock solution of Titepati performed as the best with 50.59% disease control and increase in yield by 13.51%. Therefore, three times application of 0.1% Agricinat 10 day interval starting from jointing stage can be used to control BLB disease for higher rice production.